CRIMINAL LIABILITY OF ONLINE MONEY LENDERS - Amri, Ahmad Ihsan; Fatmawati, Dr. Nynda (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2023)
Although it is most commonly associated with financial loans, a loan is a kind of liability that can include any kind of tangible asset. Similar to other debt instruments, loans involve the redistribution of financial assets over time between the debtor and the lender. Online loans are financial assistance provided by financial institutions in which the loan application is conducted using an application controlled by the financial institution. The availability of online loans makes the loan application procedure easier, faster, and less complicated. Legal research using juridical normative research methods was conducted to understand the legal issues and legal relationships of criminal liability of online lenders. This research aims to examine the effectiveness of positive law in Indonesia in law enforcement of online money lending criminal cases and examine the actions of online money lending criminal offenders who make threats, especially through cell phones, have clear legal sanctions as an effort to protect online money loan recipients. This criminal liability is in the form of punishment. There are criminal sanctions for companies or individuals including debt collectors as part of fintech lending who commit violations in the form of disclosure of personal data subject to Article 32 juncto (jo) Article 48 of the amendment to the Bill of Act on Electronic Information and Transaction.